Limit distributions for queues and random rooted trees. (1993) - Takács Takács, Lajos Lajos
Abstract : In this paper several limit theorems are proved for the fluctuations of the queue size during the initial busy period of a queuing process with one server. These theorems are used to find the solutions of various problems connected with the heights and widths of random rooted trees.